Morphology and Properties of Poly(Lactic Acid) and Ethylene-Methyl Acrylate Copolymer Blends with Organoclay - Sirirat Wacharawichanant; Sirinan Ratchawong; Phakjira Hoysang; Manop Phankokkruad (My University, 2017)
The effects of nanoclay with surface modified by 25-30 wt% of octadecylamine (Clay-ODA) on mechanical, thermal and morphological properties of poly(lactic acid) (PLA)/ethylene-methyl acrylate copolymer (EMAC) blends with various Clay-ODA contents were investigated. The EMAC with 19.60 wt% of methyl acrylate (or EMAC1820) was used, and the ratio of PLA and EMAC1820 was 80/20 by weight, and the Clay-ODA contents were 1, 3, 5 and 7 phr. The morphology analysis showed that the addition of Clay-ODA could improve the miscibility of PLA/EMAC1820 blends due to the decrease the domain sizes of dispersed EMAC1820 phase in the PLA matrix. The mechanical properties showed Young's modulus, stress at break and storage modulus of PLA/EMAC1820 blends was improved after adding Clay-ODA. The addition of Clay-ODA did not effect on the melting temperature and glass transition temperature of PLA and PLA blends. The thermal stability of PLA could improve by adding EMAC1820 and Clay-ODA.
Keywords: Organoclay; Miscibility; Thermal Stability; Methyl acrylate; Morphology; biodegradable polymer synthesis and properties